2020
DOI: 10.1155/2020/9054196
|View full text |Cite
|
Sign up to set email alerts
|

The Length and Distribution of Plasma Cell-Free DNA Fragments in Stroke Patients

Abstract: A number of studies have shown that plasma cell-free DNA is closely related to the risk of stroke, but the fragmentation status of plasma cell-free DNA and its clinical application value in ischemic stroke are still unclear. In this study, 48 patients with new ischemic stroke and 20 healthy subjects were enrolled. The second-generation high-throughput sequencing technique was used to study the plasma cell-free fragment length and regional distribution of the subjects. As noted in our results, the ratio of plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is also possible that we did not observe an increase in cfDNA because menstruation leads to DNA fragmentation to a size that cannot be amplified by the ALU-115 and the endothelial cell specific primers, which create 115 bp and 96 bp products respectively. It has been reported that cancer [33], graft transplants [34], stroke [35] as well as non-disease settings, such as pregnancy [36,37], can lead to more pronounced fragmentation of cfDNA. In the cancer context, this fragmentation can shorten cfDNA, compared to healthy controls, in both total cfDNA pool [38][39][40] and in tumour-specific fragments, from �100 bp down to 57-85 bp [32,[41][42][43].…”
Section: Plos Onementioning
confidence: 99%
“…It is also possible that we did not observe an increase in cfDNA because menstruation leads to DNA fragmentation to a size that cannot be amplified by the ALU-115 and the endothelial cell specific primers, which create 115 bp and 96 bp products respectively. It has been reported that cancer [33], graft transplants [34], stroke [35] as well as non-disease settings, such as pregnancy [36,37], can lead to more pronounced fragmentation of cfDNA. In the cancer context, this fragmentation can shorten cfDNA, compared to healthy controls, in both total cfDNA pool [38][39][40] and in tumour-specific fragments, from �100 bp down to 57-85 bp [32,[41][42][43].…”
Section: Plos Onementioning
confidence: 99%
“…Indeed, the cfDNA concentration correlates well with the severity at admission and with individual outcomes in IS patients [ 81 ] supporting meaningful measurements of plasma nuclear and mitochondrial cfDNA patterns [ 82 ] including specificity of the DNA fragmentation (300–400 bp range) profiling for diagnostic and prognostic purposes [ 77 , 81 83 ].…”
Section: Ischemic Lesions and Strokementioning
confidence: 89%
“…Some studies analysed cfDNA [ 66 – 69 ] as well as circulating miRNA panels (miR-192; -193b; -126; -130b; -221; -222) [ 70 72 ] after acute and chronic exercise. Last but not least circulating miRNA (miR-223; -21-5p; -30a-5p; -221-3p; -382-5p; -122-5p; -211-5p; PC-3p-57,664; PC-5p-12,969) [ 80 , 84 86 ], cfDNA and mtDNA could act as promising diagnostic and prognostic biomarkers of ischemic stroke [ 77 , 81 83 ].…”
Section: Pathology-specific Versus Common Cell-free Nucleic Acid Pattmentioning
confidence: 99%
“…In cases of stroke, the dynamically determined blood levels of cfDNA appear to be a valid and reliable option for establishing prognostic and diagnostic criteria [ 91 ]. While cfDNA has performed well in a number of studies as a stroke biomarker [ 92 , 93 ], none of the so-called stroke biomarkers identified to date have proven useful in medical practice, and there is still a long way to go before its clinical application, either as a standalone marker or as part of a biomarker panel.…”
Section: Cell-free Dna As a Molecular Marker Or A Diagnostic Toolmentioning
confidence: 99%